2013
DOI: 10.1155/2013/743684
|View full text |Cite
|
Sign up to set email alerts
|

Noble Metal Nanostructures Influence of Structure and Environment on Their Optical Properties

Abstract: Optical properties of nanostructured materials, isolated nanoparticles, and structures composed of both metals and semiconductors are broadly discussed. Fundamentals of the origin of surface plasmons as well as the surface plasmon resonance sensing are described and documented on a number of examples. Localized plasmon sensing and surface-enhanced Raman spectroscopy are subjected to special interest since those techniques are inherently associated with the direct application of plasmonic structures. The possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 74 publications
0
45
0
5
Order By: Relevance
“…Further increase in fluence, the same band becomes narrow (∼630 nm) with a blue shift of 20 nm. This shifting in SPR peak may be due to change in refractive index of fullerene C 60 matrix [43], as explained by Raman spectroscopy analysis that fullerene C 60 starts converting into amorphous carbon at this fluence. The energy position of the SPR peak can be predicted by using the following equation of Mie theory [21].…”
Section: Rutherford Backscattering Spectroscopy Analysismentioning
confidence: 83%
“…Further increase in fluence, the same band becomes narrow (∼630 nm) with a blue shift of 20 nm. This shifting in SPR peak may be due to change in refractive index of fullerene C 60 matrix [43], as explained by Raman spectroscopy analysis that fullerene C 60 starts converting into amorphous carbon at this fluence. The energy position of the SPR peak can be predicted by using the following equation of Mie theory [21].…”
Section: Rutherford Backscattering Spectroscopy Analysismentioning
confidence: 83%
“…Lysanov [14] proposed a theory of wave scattering on the periodic relief with an arbitrary ratio of the wavelength and spatial nonuniformity period, while Leporskii [15] verified the theoretical results [14] for the case of scattering of sound waves. Particu larly, it was shown that the angular position of diffrac tion maxima is described well by the formula (1) Here, ψ i is the incidence angle, ψ s is the reflection angle, and m is the order of the diffraction maximum. The authors of [16,17] proposed to consider a model of the scale limited fractal transfer surface, which is the linear combination of periodic functions of the form (2) as a scattering surface.…”
Section: Introductionmentioning
confidence: 99%
“…are formed by the effect of the laser radiation, ion bombardment, application of the mechanical load, and using electro chemical technologies [1][2][3][4][5][6][7][8][9][10]. These structures are interesting for using in optics, fracture and deforma tion physics, mechanics of continuous media, and in heterocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…These particles are under active research because they posses interesting physical properties differing considerably from that of the bulk phase [3][4][5]. It comes from small sizes and the ratio of surface and volume is very large [6].…”
Section: Introductionmentioning
confidence: 99%